Estandarización y optimización de insumos de pintura para la fabricación de contenedores metálicos de la empresa Great-Container de la provincia de Cotopaxi - Carvajal Moreno, Hugo Fernando (2022)
In the present investigation, the current diagnosis of the production process of metal containers of the Company "GREAT CONTAINER" was carried out in order to optimize them, reducing the waste generated in the painting area to make known to the senior management of the Company and that can see opportunities for improvement. For the investigation of the project, an approach of the propositive and quantitative critical paradigm is used with a modality of field research, bibliographic - documentary and descriptive exploratory type to obtain the necessary data. The current situation of the company was known through a field visit and for the analysis of the problems the Ishikawa and Pareto diagram is used; where the main problems in the area of repowering and painting (formulation of the mixture and mixing of paint with solvents) are evident. To standardize the processes, a number of 15 observations was determined in the painting process and 13 observations in the repowering process. With the application of the method of times and movements, it was found that the painting process occupies 86.75 minutes and 16 meters of travel and the unproductive activities are 62.59%, and 37.41% of productive activities in repowering are used 69.45 minutes and 18 meters of travel with 17.28% of unproductive activities and 82.72% of productive activities. The standard time of the painting process is 98.67 minutes with one operator, while in the repowering process it is reduced to 34.79 minutes with two operators, it also takes 133.4 minutes to produce 4 eco pans, attributing to a 1.33 echo bin per operator and 0.028 echo bin is produced per minute, the production in man hours is 2.06.